Tourism research methods : integrating theory with practice - Ritchie, Brent W.; Burns, Peter (Peter M.); Palmer, Catherine (Catherine A.) (CAB books., 2005)
This book (i) moves beyond the business/social phenomenon divide of tourism research; (ii) provides a discussion of theory but integrates this theory with specific tourism examples and case studies to assist student learning and application of approaches and techniques; (iii) outlines alternative research approaches and techniques that may be adopted by tourism researchers from different disciplines and research positions; and (iv) includes contributions from both experienced and new researchers. The book has 17 chapters and a subject index.